IMPACT OF INTERNATIONALIZATION ON HIGHER EDUCATION EFFICIENCY - Дебич, Марія (SWorldJournal, 2022)
The article contains the data on the state and trends of higher education in the European educational and scientific area and in the world. The fact of acceleration of quantitative and qualitative development of higher levels of education – training of ma